Digital Da’wah: A Religious Coping Analysis of Ismael Al-Kholilie’s Instagram - Ni Wayan Supadmi Supadmi; Adi Fadli; Dwi Wahyudiati (Mediakita, 2026)
This study examines the role of Ismael Al-Kholilie's Instagram captions as a medium for digital da'wah that facilitates religious coping and psychological resilience among contemporary Muslim social media users in Indonesia. Data were collected systematically from the public Instagram account @ismaelalkholilie from January to December 2024, focusing on posts that explicitly address spiritual guidance, adversity, resilience, and psychological well-being. The research addresses three interrelated gaps: an empirical gap in studies that examine the psychological utility of caption-based religious messaging; a theoretical gap in integrating parasocial interaction theory with religious coping frameworks; and a contextual gap in the underrepresentation of the Indonesian Muslim digital landscape in existing scholarship. Employing qualitative content analysis, the study identifies three primary religious coping dimensions embedded within the captions: Benevolent Religious Reappraisal, Collaborative Religious Coping, and Seeking Spiritual Support. Findings reveal that Benevolent Religious Reappraisal is the dominant theme, present in approximately 67% of analyzed posts, followed by Seeking Spiritual Support (21%) and Collaborative Religious Coping (12%). Audience engagement, operationalized as the mean aggregate of likes, comments, saves, and direct messages per post (M = 5,263 interactions/post), is positively associated with the presence and intensity of religious coping themes, particularly tawakkul (reliance on Allah), which consistently generates the highest save and comment rates. Language accessibility and perceived emotional authenticity are identified as critical drivers of parasocial bond formation, sustaining follower loyalty, and facilitating the dissemination of organic content. Theoretically, this study advances the interdisciplinary fields of digital religion, Islamic communication, and religious coping scholarship. Practically, it offers actionable guidance for religious educators and social media practitioners seeking to enhance spiritual growth and mental health support through online platforms.